Luke - Vinson, Richard Bolling, 1957- (Macon, Ga. : Smyth & Helwys Pub., 2008)
"The Gospel of Luke narrates the life of Jesus from the nativity stories, to Jesus' baptism and temptation, ministry in Galilee, journey to and teaching in Jerusalem, and finally his death and resurrection. In his engaging guide to Luke's account, Richard Vinson accompanies readers on their own compelling journey-a journey through the life of Christ as seen through the lenses of critical scholarship and contemporary culture. As a result, we cannot turn away from Luke's primary messages: the good news of the Kingdom of God and Jesus' emphatic teachings on wealth and poverty, repentance and forgiveness, and the role of women in Jesus' ministry...the primary goal of the Smyth & Helwys Bible Commentary series is to make available serious, credible biblical scholarship in an accessible and less intimidating format. A visual generation of believers deserves a commentary series that contains not only the all-important textual commentary on Scripture, but images, photographs, maps, works of fine art, and drawings that bring the text to life. Each volume of the Smyth & Helwys Bible Commentary series features a CD-ROM, which expands the uses and capabilities of the Commentary even more" -- From publisher description.
Introduction -- Nativity stories, part 1, Luke 1 -- Nativity stories, part 2, Luke 2 -- John's ministry, Jesus' baptism, Luke 3 -- Temptation : two sabbaths, two synagogues, Luke 4 -- Gathering disciples, Luke 5 -- Choosing twelve : Sermon on the plain, Luke 6 -- Prophetic identity, Luke 7 -- Parables, miracles, and reactions, Luke 8 -- Beginning the journey to the cross, Luke 9 -- Missionaries and householders, Luke 10 -- On prayer : negative reactions to Jesus, Luke 11 -- Teachings on hypocrisy, possessions, and servanthood, Luke 12 -- Judgment, repentance, and hope, Luke 13 -- Jesus' symposium, Luke 14 -- Three parables of finding, Luke 15 -- On possessions, Luke 16 -- Hard sayings, Luke 17 -- On prayer and possessions, Luke 18 -- Entering Jerusalem, Luke 19 -- Jesus in the temple : confrontation, Luke 20 -- Jesus in the temple : prediction, Luke 21 -- The Supper, betrayal, and arrest, Luke 22 -- The trial, Crucifixion, death, and burial, Luke 23 -- The Resurrection, Luke 24.
Includes bibliographical references (p. [761]-769) and indexes.
Print version record.
Keywords: Bible. -- Commentaries; Bible; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Commentaries; Electronic books